Oxidation of carcinogenic 2-nitroanisole by rat cytochromes P450 - similarity between human and rat enzymes - Svobodová, Martina; Dračínská, Helena; Martínková, Markéta; Hudeček, Jiří; Hodek, Petr; Frei, Eva; Stiborová, Marie (Interdisciplinary toxicology, 2008)
2-Nitroanisole (2-NA) is an important industrial pollutant and a potent carcinogen for rodents. Understanding which cytochrome P450 (CYP) enzymes are involved in its metabolism are important to assess an individual's susceptibility to this environmental carcinogen. The aim of this study was to evaluate the efficiency of rat hepatic CYPs to oxidize 2-NA, to examine the metabolites formed during such an oxidation, and to compare such efficiencies of rat CYPs with those of human. 2-NA is oxidized by rat hepatic microsomes to 2-nitrophenol (2-NP) as the major metabolite, and to 2,6-dihydroxynitrobenzene (2,6-DNB) and 2,5-dihydroxynitrobenzene (2,5-DNB) as the minor products. All these metabolites are suggested as detoxication products. Using hepatic microsomes of rats pre-treated with specific CYP inducers and microsomes from Baculovirus transfected insect cells expressing recombinant rat and human CYP enzymes we found that rat recombinant CYP2E1, 2D2, 2B2, 2C6 and 1A1, as well as orthologous human CYP enzymes are the most efficient enzymes metabolizing 2-NA. However, human CYP1A1 oxidize 2-NA with a higher efficiency than the enzyme of rats. The results show the participation of orthologous CYPs in 2-NA oxidation by both species and underline the suitability of rat species as a model to evaluate human susceptibility to 2-NA.
Keywords: 2-nitroanisole; 2-nitrophenol; metabolism; cytochrome P450; detoxication; oxidation